Accidental Periodontitis Induced by Orthodontic Treatment: A Review - Sadaf Nayab (Institute of Medico-legal Publications Pvt Ltd, 2020)
This article aims to encapsulate the effect of appliances on the periodontal health of patients undergoingorthodontic treatment. While orthodontic treatment provides benefits to a wide range of intra-oral and extraoral issues starting from aesthetics to mastication, there are some major setbacks in terms of relapse ifthe treatment is not carried out with a proper plan. Therefore, with limitations in maintaining a desiredoral hygiene, which breeds various periodontal problems, iatrogenic causes further narrow down a goodprognosis which is desired at the end of an orthodontic treatment or in fact, any medical procedure. This isa review of the unnatural and natural impact of orthodontic treatment on the tissues periodontium and thetreatments associated with it.